Der Angriff der Gegenwart auf die übrige Zeit (1985) & Vermischte Nachrichten (1986) - Kluge, Alexander (München : Edition Filmmuseum, 2010)
Der Angriff der Gegenwart auf die übrige Zeit: In this "film essay," director Alexander Kluge examines the nature of technology and (urban) identity, the intersection of film and new media in the creation of art, and the delusive quest to manipulate time. There are two different stories with both fictional and documentary aspects. In one story, a foster parent cares for a traumatized young girl who is now an orphan after witnessing a car crash that killed both her parents. After the foster-parent does the right thing and takes the girl to her aunt --her court-appointed guardian -- she is shocked to see that neither the wealthy aunt nor her servants are very interested in the girl. An unusual decision follows. In the other story, a director goes blind in the middle of a film project but has to be kept on because of his contract. This situation leads to some philosophizing on the nature of film and art in the modern world. ##Vermischte Nachrichten: This drama strings together vignettes of events taken from everyday newspaper headlines. Germans are shown in their reactions to World War II, minorities, and the elderly. A side plot follows a meeting between former West German Chancellor Helmut Schmidt and East German leader Erich Honecker. ##Special features: Disc 1. 16 Minutenfilme (17 min., 1970); Blinde Liebe: Gespräch mit Jean-Luc Godard (24 min., 2001); Zwischen Mitternacht und der vierten Nachtstund (1 min., 2006); ROM-Bereich: Filmalbum von Weinmann/ Kluge " Neonröhren des Himmels" in German. Disc 2. Frau Blackburn, geb. 5. Jan. 1872, wird gefilmt (13 min., 1967); Ein Arzt aus Halberstadt (29 min., 1970); Besitzbürgerin, Jahrgang 1908 (11 min., 1973); Nach jedem Untergang kommt ein Dampfer (1 min., 2006).
Onderzoek KASK Professioneel (OFVP)
Duits gesproken, ondertitels in Engels, Frans, Russisch, Chinees en Spaans
film
Keywords: Kluge, Alexander